Involvement of the medial pallidum in focal myoclonic dystonia: A clinical and neurophysiological case study. - Liu, X; Griffin, I; Parkin, S; Miall, R; Rowe, J; Gregory, R; Scott, R; Aziz, T; Stein, J (2002)
We successfully treated a patient with familial myoclonic dystonia (FMD), which primarily affected his neck muscles, with bilateral deep brain stimulation (DBS) to the medial pallidum, and investigated the role of the medial pallidum in FMD. A patient with FMD underwent bilateral implantation of DBS electrodes during which field potentials (FPs) in the medial pallidum and electromyograms (EMGs) from the affected neck muscles were recorded. The effects of high-frequency DBS to the medial pallidum on the FMD were also assessed by recording EMGs during and immediately after implantation, as well as 6 days and 8 weeks postoperatively. During spontaneous myoclonic episodes, increased FPs oscillating at 4 and 8 Hz were recorded from the medial pallidum; these correlated strongly with phasic EMG activity at the same frequencies in the contralateral affected muscles. The EMG activity was suppressed by stimulating the contralateral medial pallidum at 100 Hz during the operation and continuous bilateral DBS from an implanted stimulator abolished myoclonic activity even more effectively postoperatively. The phasic pallidal activity correlated with and led the myoclonic muscle activity, and the myoclonus was suppressed by bilateral pallidal DBS, suggesting that the medial pallidum was involved in the generation of the myoclonic activity. High-frequency DBS may suppress the myoclonus by desynchronising abnormal pallidal oscillations. This case study has significant clinical implications, because at present, there is no effective treatment for focal myoclonic dystonia.